2013
DOI: 10.1080/00045608.2013.834239
|View full text |Cite
|
Sign up to set email alerts
|

Ht-Index for Quantifying the Fractal or Scaling Structure of Geographic Features

Abstract: Although geographic features, such as mountains and coastlines, are fractal, some studies have claimed that the fractal property is not universal. This claim, which is false, is mainly attributed to the strict definition of fractal dimension as a measure or index for characterizing the complexity of fractals. In this paper, we propose an alternative, the ht-index, to quantify the fractal or scaling structure of geographic features. A geographic feature has ht-index h if the pattern of far more small things tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 22 publications
3
138
0
1
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 Figure 2 Fractals emerged from big data look very much like the generative fractal -Koch snowflake (Jiang 2015a) What the example illustrated are not only fractals or natural cities generated from big data, but also a new, relaxed definition of fractals. A set or pattern is fractal if there are far more small things than large ones in it, or the scaling pattern of far more small things than large ones recurs multiple times (Jiang 2015b, Jiang & Yin 2014. The new definition is in fact developed from head/tail breaks (Jiang 2013) as a classification scheme for data with a heavy tailed distribution.…”
Section: Fractals Emerged From Big Datamentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 Figure 2 Fractals emerged from big data look very much like the generative fractal -Koch snowflake (Jiang 2015a) What the example illustrated are not only fractals or natural cities generated from big data, but also a new, relaxed definition of fractals. A set or pattern is fractal if there are far more small things than large ones in it, or the scaling pattern of far more small things than large ones recurs multiple times (Jiang 2015b, Jiang & Yin 2014. The new definition is in fact developed from head/tail breaks (Jiang 2013) as a classification scheme for data with a heavy tailed distribution.…”
Section: Fractals Emerged From Big Datamentioning
confidence: 99%
“…However, while this simplistic thinking might be of little use from a physicist point of view (e.g., Bak 1996), it is of great value for mapping or understanding the underlying geographic forms and processes. Geographic forms are fractal rather than Euclidean, and the underlying geographic processes are nonlinear rather than linear (e.g., Batty and Longley 1994, Frankhauser 1994, Salingaros 2005, Benguiui and Blumenfeld-Lieberthal 2007, Chen 2009, Jiang and Yin 2014. This presents the basic perception of geographic forms and processes.…”
Section: Cognitive Mapping As An Extension Of Map-makingmentioning
confidence: 99%
“…Jiang [8] found that the NTL data followed a heavy-tailed distribution, where large values above the average were the minority, termed the head, and small values were the majority, termed the tail. This head/tail breaks method [62] iteratively divides the NTL data around the average into the head and tail parts until the head no longer represents a long-tailed distribution. This method has been verified as a universal and powerful method to delineate urban areas, namely, natural cities by Jiang [8].…”
Section: Comparison With the Head/tail Breaks Methods [8]mentioning
confidence: 99%
“…Previous studies [8] have suggested that this sensitive variable is approximately set to 60%. However, Jiang [62] noted that the sensitive variable could be modified in many cases, such as to 50% or even more. Therefore, this sensitive variable in the head/tail breaks method needs more objectivity.…”
Section: Urban Area and Accuracy Evaluationmentioning
confidence: 99%